Fractografia quantitativa: relações entre tenacidade e o comportamento fractal em ligas metálicas - Caltabiano, Pietro Carelli Reis de Oliveira [UNESP] (2011)
Fracture surface express the sequence of energy release events during crack propagation and, in the case of metallic alloys, the topographic evolution can descrbr the action of load lines, failures due to using processing, and others. In the cases, the quantitative fractography can help the investigation of failures in structures and manufacturing processes. In this work, two correlation analyses were carried out: the first between the stretch zone width (SZW) and fracture toughness (Kc) and the second between Kc and the fractality of the fractured surface topography, both analyzed by digital image processing. The 15-5PH stee and AA7475 aluminium alloy fracture surfaces for analysis were obtained by toughness testing. Each seurface was mapped by extend depth of field technique, and the following fractal dimension values were calculated for each mapped position: monofractal dimension (Df), structural dimension (Ds) and textural dimension (DT). The results for analysis between LZE and Kc data showed a high correlation for 15-5PH steel, also checking the validity of the delimitation method of SZW and the image reconstruction process. The fractal analysis showed that as higher the ductility of the material, as lower will be the level of linear correlation obtained between toughness and the fractal values. However, for 15-5PH steel, with behavior ranging between the linear-elastic and elastic-plastic, the level of linear correlation between Kc and the fractal values tend to be significant, especially for established correlations involving the textural dimension (Dt). However, for AA 7475 aluminium alloy no significant correlation could be established due to predominance of shallow dimples